EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN LEMBAR KERJA PESERTA DIDIK BERBASIS SAINTIFIK TERHADAP HASIL BELAJAR FISIKA - suarti, suarti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effectiveness of the discovery learning model assisted by LKPD based on a scientific approach to the learning outcomes of physics in fluid materials. The method used is a pre-experimental design, with a research design of one group pretest-posttest design. Based on the research that has been done, the average pretest score for learning outcomes is 71.40 in sufficient criteria. Meanwhile, the posttest average of students’ learning outcomes was 81.25, indicating that students’ learning outcomes were in good criteria. Furthermore, the results of hypothesis testing with the paired sample t-test, showed the value of sig. 0.000 which means <0.05, meaning that there is a significant difference between the learning outcomes of students before and after being given treatment. And the results of the n-gain test to determine the increase in student learning outcomes obtained the average learning outcomes before and after learning using the discovery learning learning model has increased in the medium category. This shows that the discovery learning model assisted by LKPD based on a scientific approach is effective in improving student learning outcomes.